Pengaruh Pengalaman, Independensi, dan Profesionalisme Auditor Internal Dalam Mencegah Kecurangan Pada Bank Perkreditan Rakyat - Andriyanti, Dwi; Latrini, Made Yenni (E-Jurnal Akuntansi, 2019)
This study aims to determine the effect of experience, independence, and professionalism of auditors in preventing fraud in the Rural Bank in Badung Regency. Determination of samples in this study the researchers used a saturated sampling technique. Respondents in this study were 49 people. The data collection method used is the census method with the questionnaire instrument. The results of this research questionnaire were measured using a Likert scale. The statistical method used is multiple linear regression analysis. The results of this study indicate that experience, independence and professionalism of internal auditors have a positive effect in preventing fraud in the Badung District Rural Bank. This means that the better the experience, the attitude of independence, and the attitude of professionalism the better the efforts made in preventing fraud in the People's Credit Bank (BPR) of Badung Regency. Keywords : Prevent fraud, Internal Auditor, Audit experience, Independence